Przeszłość - teraźniejszość - przyszłość, "kai eleutheria" - "kai aletheia" - "kai agathon", Platon - Nicola Chiaromonte - Wojciech Karpiński (ontologiczno-aksjologiczne trójkąty) = Past - present - future, "kai eleutheria" - "kai aletheia" - "kai agathon", Plato - Nicolai Chiaromonte - Wojciech Karpiński (ontological-axiological triangles) - Trygar, Barbara (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In the article, some ontological and axiological aspects in the artistic works of Nicola Chiaromonte and Wojciech Karpiński in the context of mathematical deliberations of Plato are being analysed. For the Greek philosopher, mathematics aided in interpreting reality, values, and questions concerning existence. The meeting with culture and Greek philosophy induced the Italian thinker and the Polish writer to contemplate "arche" with such values as freedom, truth, goodness and beauty.
Keywords: starożytność; ontologia; aksjologia; pamięć; literatura; Antiquity; ontology; axiology; memory; literature